Вы находитесь на странице: 1из 3

LESSON PLAN

I. Objectives

At the end of the lesson the students must be able to:


● Derive and solve a pair of simultaneous equation by equating two unknowns.
● Solve system of two simultaneous equations by addition and elimination
method.
● Elimination method to in prioritizing their tasks.

II. Subject Matter

A. Topic : Solving simultaneous equation algebraically


B. Grade Level : 7
C. Quarter : #3rd
D. Materials: PowerPoint Presentation, laptop, whiteboard, whiteboard marker,
cartolina, manila paper.
E. References : Math, Algebra 1-6, 1102 (ITEM #60102)

III. Procedure

● Introduction / Motivation
○ Prayer
○ Checking of Attendance
○ Checking of Assignment
○ The teacher will review about solving a system of two simultaneous
equation by substitutions.
○ The teacher will group the class into 2.
○ The teacher will give 5 sets of equations and every correct will receive
a 1 point.
○ The group that have a higher score will announce a winner.

● Interaction

 The teacher will discuss shortly that systems of equation can also
be solve by combining the equations.
 The teacher will give example and solve on board.

3𝑥 + 3𝑦 = 27
2𝑥 − 3𝑦 = 3
3𝑥 + 3𝑦 = 27
2𝑥 − 3𝑦 = 3
______________
5x = 30
x=6

 Teacher will substitute the value of x:


3x + 3y = 27
3(6) + 3y = 27
18 + 3y = 27
3y =27-18
3y =9
y=3
Solution: ( 6, 3)

 Teacher will counter check the solution


3x + 3y = 27
3(6) + 3(3) = 27
18 + 9 = 27
27 = 27
 The teacher will give more examples and the students will solve at
the board.

1) –x + y = -4
x + y = -2

2) x + y = 1
x – y = -7

● Integration

 How can you eliminate your prioritizing tasks in real life?

IV. Evaluation

Solve the equation and find the value of x and the value of y.

1) x + y = -1
x–y=3

2) x + 2y = 35
3x – 2y = 17
3) x + 2y = 12
x – 2y = 0

4) -x + y = 4
x + 3y = 8

5) 2x + 2y = 10
x – 2y = -4

V. Assignment

Solve the equation and find the value of x and the value of y.

1) 5x - 2y = 17
2x – 3y = 9

Multiply the first equation by 3


Multiply the second equation by -2

2) 4x - y = 2
8x + 5y = -3

Multiply the first equation by 5

3) 2x + 3y = 2
4x – 9y = -1

Multiply the first equation by 3

Submitted by:

Jethro P. Feria
Bema4